Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kinerja Keuangan terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia dan Masuk Peringkat CGPI Periode 2013-2015) - Widyaningrum, Novia; , Dr. Fatchan Achyani, S.E, M.Si (2017)
This research aims to investigate the influence of investment decision, financing decision, and financial performance on the firm value with good corporate governance as variable moderation in companies listed on the Indonesian stock exchange and included in the ranking CGPI the period 2013-2015. The sampling method used in this research is purposive sampling with the total sample as much as 40 companies. Analysis used by multiple regression analysis. The results showed that investment decision has a effect on firm value while financing decision and financing performance hasn't a effect on firm value. Investment decision is moderated by good corporate governance has a effect on firm value while financing decision and financing performance is moderated by good corporate governance have no effect on firm value. Keywords: investment decision, financing decision, financing performance, good corporate governanc, and firm value